ACCOUNTABILITY E AVALIAÇÃO DE SISTEMA DO BRASIL E DO URUGUAI: EM DEFESA DA QUALIDADE SOCIAL DA EDUCAÇÃO - Mello, Liliane Ribeiro De; Bertagna, Regiane Helena [UNESP]; Mancebo, María Ester (CEDES - Centro de Estudos Educação e Sociedade, 2023)
This work highlights the relationship between accountability and systems assessment, based on research on assessment policies for basic education in Brazil and Uruguay. Systems assessment has been gathering prominence within the historical-political scenario and it also shows a different unfolding in each country. This qualitative research was conducted upon the analysis of two cases (Brazil and Uruguay), document/bibliographic surveys and content analysis as well. It is inferred, consequently, that these assessments may point out to limitations towards social quality education.

Este artigo destaca as relações entre accountability e a avaliação de sistema, a partir das análises das avaliações da educação obrigatória do Brasil e do Uruguai. As avaliações de sistema ganham destaque no contexto histórico-político e se desdobram diferentemente em cada país. A pesquisa qualitativa foi desenvolvida a partir do estudo de dois casos (Brasil e Uruguai), por meio de levantamento documental e bibliográfico, e, análise de conteúdo. Entende-se que estas avaliações podem apontar para limitações no que tange à educação de qualidade social.
ACCOUNTABILITY AND SYSTEMS ASSESSMENT IN BRAZIL AND URUGUAY: ADVOCATING FOR THE SOCIAL QUALITY IN EDUCATION
Keywords: Accontability; Systems assessment Brazil; Systems assessment Uruguay; Educational assessment policies; Social quality; Accontability; Avaliação de sistemas Brasil; Avaliação de sistemas Uruguay; Políticas de avaliação educacional; Qualidade social